Physiology - Costanzo, Linda S. (Board review series, 2015)
This collection of examination questions is organized by key physiological systems, intended to support students in preparing for exams in medical or health sciences programs. The topics include: Cell Physiology – Questions cover fundamental cellular mechanisms, including membrane transport, cell signaling, and ion channel dynamics. Neurophysiology – Focuses on the function of the nervous system, including action potentials, synaptic transmission, and sensory/motor pathways. Cardiovascular Physiology – Includes questions on heart function, hemodynamics, blood pressure regulation, and cardiac output. Respiratory Physiology – Covers lung mechanics, gas exchange, control of breathing, and acid-base balance related to respiration. Renal and Acid-Base Physiology – Tests knowledge of kidney function, urine formation, and regulation of body fluid pH. Gastrointestinal Physiology – Encompasses digestive processes, nutrient absorption, and gut motility. Endocrine Physiology – Includes questions on hormonal regulation, feedback loops, and major endocrine glands. An Index is provided for quick topic referencing. This resource serves as a practical tool for self-assessment and review of core physiological concepts essential for academic success in physiology examinations.